PENGARUH PENGGUNAAN MEDIA PUZZLE STIK KATA TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN - Shentia, Shelpi Mellan; Nirmala, Ine; Rochimah, Nur (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to see how the use of word stick puzzle media can affect the ability of children aged 4-5 years to recognize letters. The focus of this study is to compile a word stick puzzle containing pictures and letter descriptions, mention and point to letters, match letters, and sort letters using word stick puzzle media. This research was carried out because there was a problem with the ability of class A children to recognize letters. This study uses a quantitative method with an experimental design. This is a type of study in which only one group is tested, without comparing it with another group. Before and after the experiment, there will be measurements taken. This study involved 16 children. In this study, the method of collecting data was carried out by observation, and to analyze the data, a simple paired t-test was used. The results of this study show that using word stick puzzle media can help children recognize letters.